2012
DOI: 10.1371/journal.pone.0043030
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serotonin, Dopamine and Norepinepherine Levels in 15q Duplication and Angelman Syndrome Mouse Models

Abstract: Childhood neurodevelopmental disorders like Angelman syndrome and autism may be the result of underlying defects in neuronal plasticity and ongoing problems with synaptic signaling. Some of these defects may be due to abnormal monoamine levels in different regions of the brain. Ube3a, a gene that causes Angelman syndrome (AS) when maternally deleted and is associated with autism when maternally duplicated has recently been shown to regulate monoamine synthesis in the Drosophila brain. Therefore, we examined mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
2
28
1
Order By: Relevance
“…Notably, a recent study showed that AS mice exhibited behavioral deficits that correlated with abnormal dopamine signaling (47). Specifically, AS mice exhibited changes in dopamine release in both the mesolimbic and nigrostriatal pathways (47), whereas another study reported increased dopamine levels in the striatum, midbrain, and frontal cortex of AS mice (48). AS mice were also shown to have a reduced number of tyrosine hydroxylase-positive neurons in the substantia nigra (10).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study showed that AS mice exhibited behavioral deficits that correlated with abnormal dopamine signaling (47). Specifically, AS mice exhibited changes in dopamine release in both the mesolimbic and nigrostriatal pathways (47), whereas another study reported increased dopamine levels in the striatum, midbrain, and frontal cortex of AS mice (48). AS mice were also shown to have a reduced number of tyrosine hydroxylase-positive neurons in the substantia nigra (10).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models of 15q11-q13 duplication and Smith-Lemli-Opitz syndromes show alterations in the central 5-HT system (Waage-Baudet et al, 2003, Nakatani et al, 2009, Farook et al, 2012, Korade et al, 2013). The BTBR inbred mouse strain, which shows many autism-relevant behavioral phenotypes, shows decreased baseline SERT binding throughout the brain and increased 5-HT 1A activity in the hippocampus (Gould et al, 2011, Gould et al, 2014).…”
Section: Mouse Models Of Asd Risk With Abnormal 5-htmentioning
confidence: 99%
“…The transmitting grandmother was found in standardized assessments of adult ADHD traits to be above the 95th percentile for impulsivity traits. Recently, Bowton et al described the transmission of the DAT Val559 variant to two, unrelated male subjects with ASD (49) that was not seen in matched unaffected subjects, extending the possible disease associations to a third disorder with evidence of DA signaling perturbations (50)(51)(52)(53)(54)(55)(56)(57).…”
mentioning
confidence: 99%